Clinical relevance of soluble HLA class I molecules in Waldenstrom Macroglobulinemia - Moreau, Anne-Sophie; Sebti, Yasmine; Duhamel, Alain; Roccaro, Aldo M.; Coiteux, Valérie; Gastinne, Thomas; Friec, Gaëlle Le; Burwick, Nicholas; Amiot, Laurence; Ho, Allen W.; Poulain, Stephanie; Hennache, Bernadette; et al. (European journal of haematology, 2008)
Objectives:  Waldenstrom Macroglobulinemia (WM) is a B‐cell neoplasm characterised by secretion of IgM by lymphoplasmacytic bone marrow cells and by cytopenias and hypogammaglobulinemia in a subset of patients. Beta‐2 microglobulin (b2m) is a major prognostic factor in WM and the heavy chain of HLA class I molecules, which are known to have immunosuppressive properties and have been implicated in the pathogeny of several malignancies. Methods:  We assessed the serum levels of the total soluble HLA‐I molecules and the HLA‐Gs molecules in 105 patients with IgM‐related disorders [WM (n = 42) and IgM MGUS (n = 63)], and compared the results to 41 healthy subjects. Results:  We found higher levels of HLA‐Is in WM, compared to IgM MGUS and healthy donors. HLA‐Gs levels were similar in WM and in IgM MGUS, but higher than in healthy donors. The association between HLA‐Is at the cut‐off of 1.8 μg/mL and known markers of poor prognosis was then evaluated among WM patients using univariate and multivariate methods. Based on this, high HLA‐Is level was strongly associated with high serum β2M level >3 mg/L [OR = 2, (CI 95% 1.1–5.7); P = 0.04], age > 65 yrs [OR = 1.5, (CI 95% 0.5–4.1), P = 0.06] and haemoglobin ≤11.5 g/dL [OR = 3.3, (CI 95% 1.2–9.7); P = 0.03]. High levels of serum HLA‐Is were also found in patients with cryoglobulinemia, however irrespectively of WM or IgM‐MGUS status. Conclusion:  Together our results suggest a possible role for soluble MHC class I molecules in WM disease. Further investigations are necessary to further demonstrate the prognostic impact of soluble MHC class I molecules in Waldenstrom Macroglobulinemia.